Multidrug-resistant, Extensively drug-resistant and Pandrug-resistant bacteria and antimicrobial therapy in combination. (Bangladesh Journal of Medical Microbiology, 2017)
Bangladesh J Med Microbiol 2015; 9 (2): 1-2